Contributions of the Parque Zoológico de Goiânia to scientific literacy: an experience report (Research, Society and Development, 2021)
This paper aimed to present the contributions of the Zoological Park of Goiânia (PZG) to the scientific literacy process. An experience carried out with 5th grade students from a school associated with the state education system of Goiás is reported. The activity was conducted in five stages: a conversation circle (for introductions and interaction between the researcher, the research and the students), a survey of the students' previous knowledge about Fauna and Flora, especially that of the Cerrado (through a questionnaire and drawings), a monitored visit to the PZG, the verification of the students' post-visit knowledge (through a questionnaire and drawings), and the socialization of this knowledge (through the production and exhibition of drawings) to the school community. The analysis of the data obtained shows that, after the visit, the students demonstrated a significant increase in their knowledge about the theme in question. The students highlighted in their drawings and answers to the questionnaires, animals and plant species that are part of the Fauna and Flora of the Cerrado, previously unknown, as well as some characteristics, which shows that the PZG is a non-formal space with great possibilities for developing learning and that contributes to the process of scientific literacy of the students who visit it.